Challenges of teaching and learning grammar in online classes at the tertiary level - Halim, Tanzina; Wahid, Rizwana; Halim, Shanjida (ELT Forum: Journal of English Language Teaching, 2021)
This paper investigates the attitude of teachers and students towards the teaching and learning of grammar for online classes. The current study aims to identify the difficulties that the students face when learning grammar through online sessions. The paper also gives an insight from teachers’ perspectives who had conducted grammar classes online. For this, 20 male and female teachers and 80 female undergraduate students of a public university in Saudi Arabia were chosen as participants to carry out the study. To find out the benefits of this shift from face-to-face classes to online classes, the instruments used were questionnaires distributed to the teachers and students who experienced online sessions for almost two semesters. Based on the findings of the results of the study, the paper concludes and gives some recommendations on how both teachers and students can cope with the challenges faced during online classes while teaching and learning grammar.